2014
DOI: 10.4103/0022-3859.132317
|View full text |Cite
|
Sign up to set email alerts
|

Is Cystatin-C superior to creatinine in the early diagnosis of contrast-induced nephropathy?

Abstract: CyC measured 48 h after contrast media exposure may be a more sensitive indicator of CI-AKI relative to creatinine and Mehran risk scoring is in good correlation with CyC increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…This early increase in serum CysC following a kidney injury is also reported in studies that investigated renal toxicity after contrast medium administration (4)(5)(6)(13)(14)(15)(16)(17)(18). In all these investigations the peak of serum CysC was significantly associated with the development of CIN occurring 24-48 hours after PCIP.…”
Section: Discussionsupporting
confidence: 52%
“…This early increase in serum CysC following a kidney injury is also reported in studies that investigated renal toxicity after contrast medium administration (4)(5)(6)(13)(14)(15)(16)(17)(18). In all these investigations the peak of serum CysC was significantly associated with the development of CIN occurring 24-48 hours after PCIP.…”
Section: Discussionsupporting
confidence: 52%
“…26 Cystatin C which is produced by all nucleated cells and freely filtered and catabolized in proximal tubules without being secreted, is also released into the circulation with a half-life of about 2 h. In other words its serum concentration is determined by glomerular filtration, so it is a better marker of glomerular filtration rate. 27 Our study shows that there is statistically significance in the value of Cys C levels between the two groups after the procedure. This sensitive marker also confirms that the iso-osmolar contrast iodixanol is less nephrotoxic than lowosmolar contrast iohexol.…”
Section: Discussionsupporting
confidence: 48%
“…Its structure is not affected by inflammation, dietary factors, sex, age or muscle mass [11,12,13]. Several studies examined the role of cystatin C in predicting CIN [14,15,16,17,18]. Ebru et al [14] showed that only cystatin C increase after contrast media exposure is in concordance with the Mehran risk scoring system for predicting the risk of CIN.…”
Section: Discussionmentioning
confidence: 63%
“…Several studies examined the role of cystatin C in predicting CIN [14,15,16,17,18]. Ebru et al [14] showed that only cystatin C increase after contrast media exposure is in concordance with the Mehran risk scoring system for predicting the risk of CIN. Another study found that baseline serum cystatin C levels significantly predicted the occurrence of CIN in patients with moderate renal insufficiency [15].…”
Section: Discussionmentioning
confidence: 84%